2019
DOI: 10.1016/j.biombioe.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of product distribution, content and fermentability of biomass in a hybrid thermochemical/biological processing platform

Abstract: Thermochemical processing is a promising method for the rapid depolymerization of biomass. This study investigated switchgrass, corn stover, red oak, hybrid poplar, and loblolly pine in terms of heteropolymer and elemental composition, and the distribution and composition of the fast pyrolysis products. Corn stover differed from other biomass types in that less of the biomass was recovered as sugar or phenolic oil (PO) and more of the biomass was recovered as bio-char and bio-gas. The sugar-rich aqueous stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
0
13
1
Order By: Relevance
“…According to Rasmussen et al (2014), the degradation of carbohydrates, especially D-glucose, D-xylose and L-arabinose can be related to the production of compounds such as phenolics. These compounds have been considered biocatalyst inhibitors (Chi et al 2019), and their gradual production according to e-beam dose increase was also observed in Lima et al (2016) study. But, in our work, the presence of phenolics did not inhibit yeast cell viability and biomass production (p>0.05) in any treatment during the fermentation (Table 3).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Rasmussen et al (2014), the degradation of carbohydrates, especially D-glucose, D-xylose and L-arabinose can be related to the production of compounds such as phenolics. These compounds have been considered biocatalyst inhibitors (Chi et al 2019), and their gradual production according to e-beam dose increase was also observed in Lima et al (2016) study. But, in our work, the presence of phenolics did not inhibit yeast cell viability and biomass production (p>0.05) in any treatment during the fermentation (Table 3).…”
Section: Resultsmentioning
confidence: 90%
“…In our study, it was not observed formation and alteration in the concentration of the inhibitors avonoids, furfural and 5-HMF (p>0.05) in any condition of treatment evaluated (Table 1). Such compounds are generally produced from sugar degradation, especially in thermal conditions (Molins 2001, Eggleston and Amorim 2006, Chi et al 2019). However, it did not occur in this study, including in the steam treatment (T5).…”
Section: Resultsmentioning
confidence: 99%
“…S1). Many of these compounds were also detected in the aqueous sugar wash solution produced in the same bio-oil recovery and processing framework [11].…”
Section: Emulsion Studiesmentioning
confidence: 93%
“…Fast pyrolysis of biomass produces several product streams: a heavy ends stream which is rich in sugars and water-insoluble phenolics, bio-char which is collected via cyclones and can be used as a soil additive, and lastly, a light ends aqueous stream rich in acetate ( Fig. 1) [66,4,11]. The water-insoluble phenolic oil stream is mainly composed of lignin-derived products, including monophenols such as phenol and syringol, in addition to higher molecular weight phenolic oligomers [4], with its composition being impacted by the pyrolysis conditions [62].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass composition varies substantially according to species (Chi et al., 2019 ), but is also impacted by growth conditions (Dennison et al., 2019 ; Templeton et al., 2009 ) and storage conditions (Smith et al., 2020 ; Towey et al., 2019 ; Wendt & Zhao, 2020 ) of the harvested biomass. Similar to the challenge of contaminants in mixed plastic wastes, harvested biomass often contains sand and soil, the presence of which can negatively impact biomass hydrolysis, often requiring the addition of a process step for their removal (Horhammer et al., 2018 ).…”
Section: Biomass and Plastic Waste Are Both Heterogenousmentioning
confidence: 99%